EFFECTS OF INTRATHECAL HYPERBARIC VERSUS ISOBARIC BUPIVACAINE IN ELECTIVE CAESAREAN SECTION - Nadia Bano; Robina Firdous (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: The aim of this study was to choose a better drug as far as effects are regarded such as rapid onset, a block that is adequate (in both extent and degree) for proposed surgery but without producing undesirable effects such as hypotension and a high block. STUDY DESIGN: A randomized control study was carried out for comparison. SETTING & DURATION: This study was conducted at department of anaesthesia and intensive care, Punjab medical college and affiliated hospitals, Faisalabad from September 2009 to June 2010. SAMPLE SIZE: The group under study consisted of 146 females aged 19 to 36 years, ASA status I & II undergoing elective cesarean section under spinal anaesthesia. METHODS: The patients were randomly allocated to receive spinal anaesthesia either by using isobaric or hyperbaric bupivacaine. Patients were monitored throughout the procedure. RESULTS: Compared with hyperbaric group haemodynamic instability was significant in isobaric group. In our study frequency of hypotension was 24.7% in isobaric group (group A) as compared to 9.6% in hyperbaric group (group B). Extra fluids and vasopressors were required more frequently in isobaric group. While assessing the quality of block, the onset of block was more rapid in hyperbaric group, however both drugs offered adequate anaesthesia for proposed surgery. CONCLUSION: It is suggested that hyperbaric bupivacaine is associated with adequate Intrathecal block with greater haemodynamic stability in patients undergoing elective caesarean section.